1989
DOI: 10.1016/s0022-5347(17)39048-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Analysis and Uroflowmetry 7 Years After Transurethral Resection of the Prostate

Abstract: The long-term result after transurethral resection of the prostate is not well documented. From 1981 to 1983, 84 consecutive consenting patients completed detailed symptom analysis and urodynamic examination before transurethral resection of the prostate. These studies were repeated 3 and 12 months postoperatively. Of the 84 patients 44 were interviewed at 86 months: 75% reported improvement compared to preoperative symptoms. In addition, 23 patients underwent uroflowmetry at 7 years. For this group the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 13 publications
5
31
1
1
Order By: Relevance
“…Worry about retention before and 12 months after pros tate surgery report any particular symptom before surgery are likely to say it seldom or never occurs after surgery. These results correspond with comparable reports in the literature [11,12].…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Worry about retention before and 12 months after pros tate surgery report any particular symptom before surgery are likely to say it seldom or never occurs after surgery. These results correspond with comparable reports in the literature [11,12].…”
Section: Methodssupporting
confidence: 93%
“…As we have seen, nearly 90% of those who reported symptom frequency alone. Studies of the rela tionship between the physiology of the prostate and blad der and symptoms observed by patients do not indicate strong correlations [12]. Our data show major differences among patients in how particular symptoms affect their quality of life.…”
Section: Discussioncontrasting
confidence: 58%
“…reported long-term results after transurethral resection of the prostate in 84 patients. 11 In their study, symptom scores changed from 16 at baseline to 4 at 3 months and 4 at 7 years. Maximum urine flow rate also changed from 9.5 mL/s at baseline to 17.0 mL/ s at 3 months and 12.2 mL/s at 7 years.…”
Section: Discussionmentioning
confidence: 96%
“…In this rather small series, TUR/P and VLAP led to compa rable results [28], De Wildt et al [29] determined the uro dynamic effect of 3 different laser devices 6 months after therapy. For all three devices significant improvements of weight after TUR/P can be generated, particularly as we have excluded large glands [32,33], This raises the issue, why the clinical results are not closer to TUR/P and two explanations are possible. Postoperative endoscopies demonstrated that obstructive tissue was often present at the bladder neck, while cavities were frequently identified in the prostatic urethra.…”
Section: Discussionmentioning
confidence: 96%